Dimensi Moral Dalam Profesi Advokat dan Pekerjaan Bantuan Hukum - Winarta, Frans Hendra (LAW REVIEW, 2002)
"Profesionalism without ethics results in "Free winged" (vleugel vri). It means that such professionalism will lead to the absence of orientation and direction. In contrary, ethics without professionalism result in "broken winged" (vleugel law), meaning that such ethics will never develop and fail to stand upright.3 Â There issues of law and justice are no longer dealing with technical-procedural issues in determining whether or not an action is challenging the prevailing laws or the Indonesian tenet law. Current issues in this third world go beyond them and concern more on preparing what are not yet available and adapt with those which fit the legal tranplantation process within the development process of new economic order. This paper will further see the moral dimensions of the profession of lawyers and legal advisors which closely related to meanings, functions and the roles of lawyers including the ethical codes which govern the profession.Â